Peningkatan Peningkatan kemampuan Siswa XII - A - 1 SMAN - 3 Atambua Berbicara Bahasa Inggris melalui Dialog berpasangan (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The aim of this research was to find out the effect implementation listening while reading (LWR) strategy to enhance student’s reading fluency and comprehension of the seventh grade students at SMP Y.P Keluarga Pematangsiantar in the academic year 2021/2022. This research used quantitative approach with true experimental design. The data were obtained by using pre-test and post-test. The data of the pre-test and post- test of both groups were analyzed by using descriptive and inferential statistics (SPSS 26.0). the data to be analyzed are frequency, statistic, normality, homogeneity and hypothesis testing. The result of the research shows that the testing hypothesis of post-test scores, it is found that Tcount =5.663 > Ttable = 1.699 at the significance level a = 0.05 and degrees of freedom (df) = 29. So, H0 is rejected and Ha is accepted. It means that, the implementation of LWR effect significantly on students' reading fluency and comprehension abilities at seventh grade of Y.P. Keluarga Pematangsiantar in academic year 2021/2022